The National Intelligence Agency (NIA) and Nigeria’s Diplomatic Relations in Contemporary Times - Sunday, Adejoh; Shimawua, Dominic (NIU Journal of Humanities; Vol 3 No No. 2 (2018): KIU Journal of Humanities, Vol. 3 No. 2, June 2018, 2018)
International politics in an integral component of the international system with each state making moves to promote project and protect their national interest. In a bid to further promote state relations embassies and consulates are established in different countries to serve as formal institutional and symbolic presence of states outside their state hence, overtly and covertly pursuing their national interest. Intelligence, Diplomacy and foreign policies are key instruments in all these processes. This work therefore is an attempt to interrogate the role of the National intelligence Agency in Nigeria diplomatic relations with a view to identifying the strategic importance of this agency while x-raying the political and diplomatic underpinnings that characterise the politics among nations. This paper relies on the secondary data and Gabriel Almond’s theory of structural functionalism as instruments for analysis. This paper further posit that the National intelligence Agency (NIA) is pivotal to Nigeria’s diplomatic relations and in the final analysis recommends the need to ensure that employees of NIA are experts either in international relations or strategic studies. Keywords: International Politics, Foreign Policy, Diplomacy, National Interest, Espionage